2019
DOI: 10.1002/mma.6098
|View full text |Cite
|
Sign up to set email alerts
|

Stability and bifurcation analysis of a nutrient‐phytoplankton model with time delay

Abstract: We proposed a nutrient‐phytoplankton interaction model with a discrete and distributed time delay to provide a better understanding of phytoplankton growth dynamics and nutrient‐phytoplankton oscillations induced by delay. Standard linear analysis indicated that delay can induce instability of a positive equilibrium via Hopf bifurcation. We derived the conditions guaranteeing the existence of Hopf bifurcation and tracked its direction and the stability of the bifurcating periodic solutions. We also obtained th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
(113 reference statements)
0
5
0
Order By: Relevance
“…Due to the complexity and openness of real aquatic ecosystems, establishing mathematical models is now a classical way to study the planktonic blooms, 15 which can provide quantitative insights into the dynamic mechanisms of changes in plankton populations. In recent years, many deterministic mathematical models for plankton dynamics, such as delayed nutrient-phytoplankton models, 16,17 a diffusive nutrient-toxic phytoplankton model, 18 viral infection nutrient-phytoplankton models, 19,20 a phytoplankton-toxin-producing phytoplankton-zooplankton model, 13 and so on, have been developed and studied extensively, and many interesting results have been shown. However, plankton populations in real aquatic environments often fluctuate unpredictably because of the unpredictability of environmental stochasticity, and these deterministic models do not capture the random environmental fluctuations which is an important feature of aquatic ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complexity and openness of real aquatic ecosystems, establishing mathematical models is now a classical way to study the planktonic blooms, 15 which can provide quantitative insights into the dynamic mechanisms of changes in plankton populations. In recent years, many deterministic mathematical models for plankton dynamics, such as delayed nutrient-phytoplankton models, 16,17 a diffusive nutrient-toxic phytoplankton model, 18 viral infection nutrient-phytoplankton models, 19,20 a phytoplankton-toxin-producing phytoplankton-zooplankton model, 13 and so on, have been developed and studied extensively, and many interesting results have been shown. However, plankton populations in real aquatic environments often fluctuate unpredictably because of the unpredictability of environmental stochasticity, and these deterministic models do not capture the random environmental fluctuations which is an important feature of aquatic ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the study of differential equations with delays are more general than ordinary differential equations [17][18][19][20][21][22][23][24]. For example, a nutrient-phytoplankton interaction model with a discrete and distributed time delay was considered in Guo et al [18]. Zhang et al [20] studied the dynamic characteristics of fractional-order three-dimensional nonlinear financial system with delay.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with general differential equations, equation with delays are more complex and more accurate to describe the state of dynamic systems. Therefore, the study of differential equations with delays are more general than ordinary differential equations [17][18][19][20][21][22][23][24]. For example, a nutrient-phytoplankton interaction model with a discrete and distributed time delay was considered in Guo et al [18].…”
Section: Introductionmentioning
confidence: 99%
“…Actually, many mathematical models have been constructed to study the dynamical behaviors of plankton since the pioneering work of Riley et al (1949), and many physical and biological processes underlying the mechanisms of plankton dynamics in the aquatic environments have been investigated (Huppert et al 2002;Dai et al, 2016;Caperon, 1969;Guo et al, 2019;Lin et al, 2005;Zhao et al, 2020). For example, in order to study how the nutrient affects the dynamics of phytoplankton blooms, Huppert et al (2002) presented a simple nutrient-phytoplankton model and identified an important threshold effect that a bloom will only be triggered when nutrients exceed a certain defined level using mathematical model analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complexity and openness of real aquatic ecosystems, establishing mathematical models is now a classical way to study the planktonic blooms (Truscott and Brindley, 1994), which can provide quantitative insights into the dynamic mechanisms of changes in plankton populations. In recent years, many deterministic mathematical models for plankton dynamics, such as delayed nutrient-phytoplankton models (Dai et al, 2016;Guo et al, 2019), a diffusive nutrient-toxic phytoplankton model (Chakraborty et al, 2015), viral infection nutrient-phytoplankton models (Li and Gao, 2016;Chattopadhyay et al, 2003), a phytoplankton-toxin producing phytoplankton-zooplankton model (Chattopadhyay et al, 2004), and so on, have been developed and studied extensively, and many interesting results have been shown.…”
Section: Introductionmentioning
confidence: 99%